2022
DOI: 10.31223/osf.io/eagqd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lateral variability of shelf-edge, slope and basin-floor deposits, Santos Basin, offshore Brazil

Abstract: Construction of continental margins is driven by sediment transported across the shelf to the shelf-edge, where it is reworked by wave-, tide- and river-influenced processes within deltas and flanking clastic shorelines. Stalling of continental margin progradation often results in degradation of the outer shelf to upper slope, with re-sedimentation to the lower slope and basin-floor via a range of sediment gravity-flows and mass-movement processes. Our understanding of how these processes contribute to the lon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…Mass transport deposits/hemipelagic fall-out in clinoform bottomsets Early Palaeogene, Santos Basin, Brazil (Steventon et al, 2019 footwall cut-off point and the observed hangingwall cut-off (Figure 4). 'Minimum' fault throw is provided by measuring the distance between the highest preserved point on the fault scarp to the hangingwall cut-off; omitting the eroded part of the fault scarp in the measurement (Figure 4).…”
Section: Sf5mentioning
confidence: 98%
“…Mass transport deposits/hemipelagic fall-out in clinoform bottomsets Early Palaeogene, Santos Basin, Brazil (Steventon et al, 2019 footwall cut-off point and the observed hangingwall cut-off (Figure 4). 'Minimum' fault throw is provided by measuring the distance between the highest preserved point on the fault scarp to the hangingwall cut-off; omitting the eroded part of the fault scarp in the measurement (Figure 4).…”
Section: Sf5mentioning
confidence: 98%
“…Mass transport deposits/hemipelagic fall-out in clinoform bottomsets Early Palaeogene, Santos Basin, Brazil (Steventon et al, 2019).…”
Section: Sf5mentioning
confidence: 99%